1986
DOI: 10.1161/01.res.58.2.209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of systolic bulging. Mechanical characteristics of acutely ischemic myocardium in the conscious dog.

Abstract: SUMMARY. To determine the mechanical factors affecting regional segmental motion after acute coronary occlusion, we studied seven conscious dogs, instrumented with sonomicrometers. Loading conditions were changed by the withdrawal of 500 ml of blood and the transfusion of 800 ml of blood. To express segmental motion, percent systolic shortening, percent systolic elongation, and early diastolic shortening were calculated. Blood withdrawal decreased left ventricular preload, increased percent systolic elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1
2

Year Published

1988
1988
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(26 citation statements)
references
References 31 publications
0
23
1
2
Order By: Relevance
“…14,32 However, in the present study, an increase in left ventricular enddiastolic volume resulted in further decreases in systolic area shrinkage and regional work in the ischemic region. This suggests that the ischemic region does not always behave as a completely passive material.…”
Section: Discussioncontrasting
confidence: 60%
“…14,32 However, in the present study, an increase in left ventricular enddiastolic volume resulted in further decreases in systolic area shrinkage and regional work in the ischemic region. This suggests that the ischemic region does not always behave as a completely passive material.…”
Section: Discussioncontrasting
confidence: 60%
“…All length values were normalised by assuming segment length at end diastole in control to be 10 mm. 18 …”
Section: Sonomicrometrymentioning
confidence: 99%
“…In the work of Akaishi et al 4 and that of Lew et al ,8 the influence of preload on the movement of ischemic and nonischemic myocardium was demonstrated. In the present study we undertook the analysis of the influence of afterload on systolic bulging and augmentation of nonischemic myocardium.…”
mentioning
confidence: 95%
“…1 4 showed how bulging occurred predominantly during isovolumetric shortening and that the slight inward motion of ischemic myocardium during ejection systole was passive. They further demonstrated that the extent of bulging depended on preload, and this dependence could be explained by the exponential shape of the tension-length relationship.…”
mentioning
confidence: 99%